BUILDING TEACHERS' CREATIVITY IN LEARNING DEVELOPMENT THROUGH TRANSFORMATIONAL LEADERSHIP AND KNOWLEDGE SHARING IN THE PANDEMIC ERA IN STATE ELEMENTARY SCHOOLS IN THE EAST JAKARTA REGION - Unifah Rosyidi; Nurhattati Nurhattati; Rahmatiah Rahmatiah (LPPM Universitas Negeri Jakarta, 2022)
Efforts to increase teacher creativity have an impact on students, especially in improving students' thinking skills to be creative. This study explains the creativity of teachers in teaching during the covid 19 pandemic. The method in this study uses a quantitative method that explains the relationship between variables using Structural Equation Modeling Partial Least Square (SEMPLS) based on variance. Respondents in this study were Madrasah teachers in West Java-Indonesia using an online survey. The results of this study indicate that transformational leadership and knowledge sharing influence teacher creativity. In the end, this study provides input for schools to give full attention to these variables in increasing teacher creativity that can be used to increase student creativity.